2012
DOI: 10.1002/ajmg.a.35270
|View full text |Cite
|
Sign up to set email alerts
|

KRAS gene mutations in Noonan syndrome familial cases cluster in the vicinity of the switch II region of the G‐domain: Report of another family with metopic craniosynostosis

Abstract: Noonan syndrome (NS) and Noonan-related disorders [cardio-facio-cutaneous (CFC), Costello, Noonan syndrome with multiple lentigines (NS-ML), and neurofibromatosis-Noonan syndromes (NFNS)] are a group of developmental disorders caused by mutations in genes of the RAS/MAPK pathway. Mutations in the KRAS gene account for only a small proportion of affected Noonan and CFC syndrome patients that present an intermediate phenotype between these two syndromes, with more frequent and severe intellectual disability in N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 34 publications
1
16
0
Order By: Relevance
“…The main pathogenic variants of Noonan syndrome are caused by mutations in PTPN11 (50%) (Tartaglia, Cotter, Zampino, Gelb, & Rauen, or SOS1 (13%) (Roberts et al, ), whereas those of CFC syndrome are associated with mutations in BRAF (47%) or MAPK2K1 (9.8%) (Schulz et al, ). The previously reported patients with craniosynostosis and Noonan syndrome were caused by KRAS mutations (Addissie et al, ; Brasil et al, ; Kratz et al, ; Lo et al, ; Schubbert et al, ). In the present study, patients 5 and 6, who had CFC syndrome caused by mutations in KRAS , had more severe craniosynostosis (i.e., all of their cranial sutures were affected by synostosis) than the patients with BRAF or PTPN11 mutations.…”
Section: Discussionmentioning
confidence: 97%
“…The main pathogenic variants of Noonan syndrome are caused by mutations in PTPN11 (50%) (Tartaglia, Cotter, Zampino, Gelb, & Rauen, or SOS1 (13%) (Roberts et al, ), whereas those of CFC syndrome are associated with mutations in BRAF (47%) or MAPK2K1 (9.8%) (Schulz et al, ). The previously reported patients with craniosynostosis and Noonan syndrome were caused by KRAS mutations (Addissie et al, ; Brasil et al, ; Kratz et al, ; Lo et al, ; Schubbert et al, ). In the present study, patients 5 and 6, who had CFC syndrome caused by mutations in KRAS , had more severe craniosynostosis (i.e., all of their cranial sutures were affected by synostosis) than the patients with BRAF or PTPN11 mutations.…”
Section: Discussionmentioning
confidence: 97%
“…We report a child with Noonan syndrome due to a KRAS mutation (p.P34Q) and sagittal craniosynostosis and review all reported cases of RASopathies to identify similar patients with craniosynostosis. Including the present report, from a total of 62 cases of RASopathies with KRAS mutations, six patients had NS and craniosynostosis [Schubbert et al, ; Kratz et al, ; Lo et al, ; Brasil et al, ]. This suggests that individuals with Noonan syndrome associated with KRAS mutations have an increased risk for craniosynostosis with 1 of every 10 published cases of KRAS mutations having craniosynostosis; this is greater than 300 times the prevalence in the general population.…”
Section: Discussionmentioning
confidence: 68%
“…The p.P34Q KRAS mutation in the present patient has been reported in another individual affected with NS without craniosynostosis [Zenker et al, ], demonstrating variable expressivity of the p.P34Q mutation. With the exception of patient two in Kratz et al [], the previously reported mutations in patients with NS and craniosynostosis had also been reported in NS patients without craniosynostosis [Schubbert et al, ; Nava et al, ; Brasil et al, ]. These reports indicate that there are other genetic or environmental modifiers that influence the described abnormal cranial development.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations